Clinicopathological Features of Thyroid-Like Low-Grade Nasopharyngeal Papillary Adenocarcinoma: A Case Report and Review of the Literature - Takakura, Hiromasa; Hamashima, Takeru; Tachino, Hirohiko; Nakazato, Akira; Minato, Hiroshi; Sasahara, Masakiyo; Shojaku, Hideo (Frontiers in Surgery, 2020)
Thyroid-like low-grade nasopharyngeal papillary adenocarcinoma (TL-LGNPPA) is an extremely rare neoplasm of the nasopharynx. Accordingly, its clinical and pathological characteristics are not well-known. We report a case of TL-LGNPPA and review the relevant literature on TL-LGNPPA. A 38-year-old Japanese woman presented with a history of nasal obstruction that had persisted for 1 month after symptoms of a common cold (e.g., low-grade fever, sore throat, and fatigue). A pedunculated tumor of ~20 mm in diameter was found on the posterior edge of the nasal septum. The tumor was endoscopically resected. Based on careful histopathological and immunohistochemical examinations, it was diagnosed as TL-LGNPPA. At 5 years after surgery, the patient remained disease-free. TL-LGNPPA has a very good prognosis, and complete resection with a sufficient safety margin is recommended as the first-line treatment. The morphological characteristics and immunohistochemical findings, especially TTF-1 positivity and thyroglobulin negativity, are important for the diagnosis.